MICROBIAL SUCCESSION DURING THE FERMENTATION OF SEMERU ARABICA COFFEE IN WINE COFFEE PRODUCTION - Sriherfyna, Feronika Heppy; Khairanny, Neysa Nurjananah; Nurcholis, Mochamad; Maligan, Jaya Mahar (Jurnal Pangan dan Agroindustri, 2024)
The current trend in coffee product diversification is wine coffee, which has a wine-like flavor and aroma. Reviews of wine coffee are still limited, especially those related to microbial succession during the fermentation process. The objective of this research was analyzing the microbial population and the effect of microbial succession during fermentation process of Arabica Semeru coffee. The analysis was conducted by identifying microbes microscopically and macroscopically. The results of microbial identification during the 30-day fermentation showed populations of yeast, lactic acid bacteria, and acetic acid bacteria. Along with the length of fermentation time, the temperature decreased and the pH fluctuated and stabilized after 16 days of fermentation. There was an increase in sugar and protein content, from 0.61% to 2.87% and 2.13% to 2.23%, respectively. The ethanol content reached 0.047% at the end of fermentation. The microbial exploration was required for further investigation in understanding its role during fermentation process.